The Quintessence of Strategic Management What You Really Need to Know to Survive in Business - Kotler, Philip; Berger, Roland; Bickhoff, Nils.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Having read this book: You will have a basic understanding of strategy and the process of strategic management. You will know the most important strategy tools (incl. the respective original literature) and how they interact. You will be aware of the focal areas and considerations of strategy in practice. You will be able to analyze and interpret business information with regard to the underlying strategic notions.
Strategy and Strategic Management: A First Basic Understanding -- Strategic Frames of Reference: The Key Tools of Strategy Determination, their Principles, and How they Interact -- Current Focal Areas in Strategy Practice: Four Significant Management Concepts of the Past 20 Years.
Keywords: Economics; Industrial management; Entrepreneurship; Economics/Management Science; Management/Business for Professionals; Business/Management Science, general; Entrepreneurship